Condensation properties of water vapor under different back pressures in nozzle. (March 2022) - Yin, Pengbo; Li, Tingting; Cao, Xuewen; Teng, Lin; Li, Qigui; Bian, Jiang
Abstract: The existence of back pressure at outlet has a direct impact on the separation performance of the separation separator. However, the influence of back pressure is not understood well due to the complicated interaction of the supersonic flow, condensation and shock waves. In this study, the condensation flow models of water vapor were established, the influence of back pressure on supersonic condensation properties of water vapor was investigated. The results show that when the back pressure exists, the position of the shock wave is more forward than that without condensation, and the strength of shock wave is weaker. The nucleation rate is generated around the position of x  = 115 mm and increases sharply from 0 to 10 25  m −3  s −1 . The shock wave is generated at x  = 145 mm and x  = 122 mm when the outlet back pressure is 20 kPa and 30 kPa, respectively. The condensed droplets evaporate again with the effect of shock wave, and then the secondary condensation of droplets occurs owing to the cooling effect of nozzle. When the back pressure is higher than a certain value, the refrigeration environment in the nozzle is completely destroyed with the effect of shock wave, and the condensed droplets evaporate again.